Association of Postoperative Hyperbilirubinemia and Infection Among Patients Undergoing Emergency Exploratory Laparotomy for Gastrointestinal Perforation at Tertiary Care Hospital Karachi: Postoperative Hyperbilirubinemia and Infection in Emergency Laparotomy for GI Perforation - Arshad, Qurrat Ul Ain; Ansari, Shireen Sabir; Naeem, Maida; Jhatial, Shakila; Lodhi, Maleeha Khan; Keen, Irfan Tariq; Sabtan, Deema (Pakistan Journal of Health Sciences, 2025)
Patients presenting to the surgery emergency room complaining of severe abdominal discomfort are often patients with gastrointestinal perforations. In the developing world, there are differences in incidence, site of perforation, aetiology, and demographics. Because of the distinct pathophysiologies associated with elevated levels of direct bilirubin (D-Bil) and indirect bilirubin (I-Bil), the consequences related to these two forms of bilirubin are likewise distinct. Objectives: To determine the association of postoperative hyperbilirubinemia and infections among patients undergoing emergency exploratory laparotomy for gastrointestinal perforation at Tertiary Care Hospital, Karachi. Methods: This prospective cohort study utilized a non-probability convenience sample in a one-year cohort study that took place at the Department of Surgery, Dr. Ruth K.M. Pfua Civil Hospital in Karachi. The SPSS software (version 26) was used for data processing. The t-test was applied, and the p-value was determined to be less than or equal to 0.05. Results: Postoperative infection showed that in the patients who were in the exposed and unexposed groups, 24 (48%) and 15 (30%) had postoperative infection. P-value was 0.006 with a relative risk of 1.60. Mortality showed that in the patients who were in the exposed and unexposed group, 13 (26%) and 02 (4%) had mortality. P-value was 0.001 and a margin of relative risk 6.50. Conclusions: The results show that patients with GI perforation who experience postoperative hyperbilirubinemia are more likely to have persistent postoperative infection and have a worse prognosis.